Personal wellbeing among adolescents and youth in India - Ratra, Dhriti; Singh, Kamlesh (Frontiers in Psychology, 2022)
This study sought to explore the level of personal wellbeing and identified the determinants of happiness among Indian adolescents and youth. Data were collected from a sample of 495 participants (aged 11–23 years) residing in the National Capital Region of Delhi (Delhi-NCR), using the bilingual version (Hindi and English) of the Personal Wellbeing Index (PWI). Their PWI score was 80.06, indicating high happiness levels in the nonwestern normative PWI range. Domains of personal relationships, community connectedness, and safety represented high overall wellbeing with the highest mean scores. Multivariate analysis showed that the least happy group on life as a whole domain was students aged 19–23 years as compared with the 11–14 and 15–18 years age group. Furthermore, men had higher happiness levels on personal safety, while women had higher scores on life achievement. The qualitative analysis illustrated the socio-cultural basis of these wellbeing determinants as rooted in the hierarchical social structures and collectivistic cultural orientation.